Fresh in My Mind! Investigating the effects of the order of presenting opportunistic and restrictive design for additive manufacturing content on students' creativity. (3rd April 2021) - Prabhu, Rohan; Simpson, Timothy W.; Miller, Scarlett R.; Meisel, Nicholas A.
Abstract : To capitalise the design freedoms enabled by additive manufacturing (AM), designers must employ opportunistic and restrictive design for AM (O- and R-DfAM respectively). The order of information presentation influences the retrieval of said information; however, there is a need to explore this effect within DfAM. We compared four variations in DfAM education: (1) O-DfAM followed by R-DfAM, (2) R-DfAM followed by O-DfAM, (3) only O-DfAM, and (4) only R-DfAM by evaluating: (1) students' DfAM self-efficacy, (2) their self-reported DfAM use, and (3) design creativity. All students trained in DfAM demonstrated an increase in R-DfAM self-efficacy; however, only students trained in O-DfAM, with or without R-DfAM, reported an increase in O-DfAM self-efficacy. Furthermore, students trained in R-DfAM first followed by O-DfAM generated more creative ideas.